Bibliometric Studies in Education: Systematic Review 2018-2022 - Velarde-Molina, Jehovanni Fabricio; Said-Hung, Elias Manuel; Laura-De La Cruz, Kevin Mario; Delgado Rospigliosi, Marjorie Gabriela (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
A thorough evaluation of the scientific literature is used in the study to assess. The methodology was based on the implementation of the PRISMA statement's guiding principles. The findings showed that 2021 will see the greatest amount of research produced, with English being the most common language, Spain being the largest producer, the United Kingdom having the most journals, and the employment of augmented reality being the most explored tactic. A number of bibliometric studies have been conducted to highlight the evolution of these studies through time in the field of education science, and more specifically in the methodology applied to education.